Resonance features of microwave waveguide Bragg structures - D.A. Usanov; S.A. Nikitov; A.V. Skripal; M.K. Merdanov; S.G. Evteev; D.S. Ryazanov; D.V. Ponomarev (Физика волновых процессов и радиотехнические системы, 2018)
The appearance of resonance features, which are analogs of Tamm surface states, in the one-dimensional waveguide Bragg structure of the microwave range, composed of two series-connected Bragg structures with different sizes of elementary cells and made in the finn-line form has been investigated. The possibility of using the reflective properties of Bragg structures with resonant diaphragms in a circuit with a Y-circulator has been demonstrated to create rejection filters with controlled by n-i-p-i-n-diodes frequency characteristics with locking level in the stop band of more than 43 dB and losses outside the band less than 0.8 dB.